2005
DOI: 10.1007/s00125-005-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the E23K polymorphism in the KCNJ11 gene with gestational diabetes mellitus

Abstract: Aims/hypothesis: Gestational diabetes mellitus (GDM) and type 2 diabetes share a common pathophysiological background, including beta cell dysfunction and insulin resistance. In addition, women with GDM are at increased risk of developing type 2 diabetes later in life. Our aim was to investigate whether, like type 2 diabetes, GDM has a genetic predisposition by studying five common polymorphisms in four candidate genes that have previously been associated with type 2 diabetes. Materials and methods: We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 46 publications
4
77
1
1
Order By: Relevance
“…Given the influence of the variant on insulin secretion [14,15,17] and our previous findings of associations of KCNJ11 E23K, GCK 30G>A and TCF1 I27L [10,11] variants with gestational diabetes mellitus, this finding supports the central role of impaired beta cell function in the pathogenesis of gestational diabetes mellitus [3].…”
Section: Adrb3 Trp64argsupporting
confidence: 81%
See 2 more Smart Citations
“…Given the influence of the variant on insulin secretion [14,15,17] and our previous findings of associations of KCNJ11 E23K, GCK 30G>A and TCF1 I27L [10,11] variants with gestational diabetes mellitus, this finding supports the central role of impaired beta cell function in the pathogenesis of gestational diabetes mellitus [3].…”
Section: Adrb3 Trp64argsupporting
confidence: 81%
“…Scandinavian) and were recruited from the same place and during the same time period. The characteristics of the majority of participants in the present study have been reported earlier [10]. Detailed phenotypic characteristics, including OGTT data, were available only for a small proportion of the women with gestational diabetes mellitus [31].…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined candidate genes in women with and without GDM. Positive associations were shown for genes encoding glucokinase [11], calpain-10 [12], sulfonylurea receptor 1 [13], potassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) [14], β 3 adrenergic receptor [15], plasminogen activator inhibitor 1 [16] and transcription factor 7-like 2 (TCF7L2) [17,18]. Except for the effects of TCF7L2 in Scandinavian women [17], no robust associations of genetic variants with GDM have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda farklı popülasyonlarda KCNJ11 genindeki polimorfizmlerin GDM ile ilişkili olduğuna dair çalış-malar da rapor edilmiştir (32)(33)(34) …”
Section: Discussionunclassified